Stock Valuation Analysis of Islamic Bank in Related to Forming Holding - Anton Adventus Kacaribu (Faculty of Economic and Business, 2020)
This study aims to estimate the fair value of equity per share and to analyze undervalued or overvalued value of the company PT. Bank BRI Syariah Tbk. Result on this study combine market approach, book value approach and discount of future cash flow approach, so it can deliver comprehensive result. On the other side, this study or valuation specialize on financial industry due to uniqueness and complexity of the industry. PT. Bnk BRI Syariah Tbk was chosen, because of the plan ot the ministry of state-owned enterprises of the Republic of Indonesia to merge 3 sharia banks such as PT Bank BRI Syariah Tbk, PT Bank Syariah Mandiri, and PT Bank BNI Syariah. Only, PT Bank BRI Syariah is public company. This research is a descriptive analysis, the data and information used are secondary data from PT Bank BRI Syariah Tbk through its annual report, while other data used come from data and reports from other supporting institutions. This study uses three methods to value the share, free cash flow to equity, relative valuation, and abnormal earning. The conclusion is fair value of PT Bank BRI Syariah Tbk is IDR 482.47, so the value is undervalued.